How many suns are in the sky? Multiplicity surveys of exoplanet host stars. Issue Volume 14:Issue S345(2019) (August 2018) - Mugrauer, M.; Ginski, C.; Vogt, N.; Neuhäuser, R.; Adam, C.
Abstract: In order to determine the true impact of stellar multiplicity on the formation and evolution of planets, we initiated direct imaging surveys to search for (sub)stellar companions of exoplanet host stars on close orbits, as their gravitational impact on the planet bearing disk at first and on formed planets afterwards is expected to be maximal. According to theory these are the most challenging environments for planet formation and evolution but might occur quite frequently in the milky way, due to the large number of multiple stars within our galaxy. On this poster we showed results, obtained so far in the course of our AO and Lucky-imaging campaigns of exoplanet host stars, conducted with NACO/ESO-VLT for southern and with AstraLux/CAHA2.2m for northern targets, respectively. In addition, we introduced our new high contrast imaging survey with SPHERE/ESO-VLT to search for close companions of southern exoplanet host stars, and presented some first results.